2009
DOI: 10.1016/j.str.2009.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Structure of the Eukaryotic Ribosome

Abstract: Despite the emergence of a large number of X-ray crystallographic models of the bacterial 70S ribosome over the past decade, an accurate atomic model of the eukaryotic 80S ribosome is still not available. Eukaryotic ribosomes possess more ribosomal proteins and ribosomal RNA than bacterial ribosomes, which are implicated in extra-ribosomal functions in the eukaryotic cells. By combining cryo-EM with RNA and protein homology modeling, we obtained an atomic model of the yeast 80S ribosome complete with all ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(178 citation statements)
references
References 77 publications
(112 reference statements)
5
173
0
Order By: Relevance
“…4A), as predicted previously by Alkemar and Nygård (25). Although this interaction was not modeled in the fungal or canine 80S ribosomes (23,24), covariation analysis suggests that the ES3 S -ES6 S base-pairing interaction is also conserved in mammalian 80S ribosomes (25).…”
Section: Comparison Of Expansion Segments Between Yeast and Wheat Germsupporting
confidence: 74%
See 2 more Smart Citations
“…4A), as predicted previously by Alkemar and Nygård (25). Although this interaction was not modeled in the fungal or canine 80S ribosomes (23,24), covariation analysis suggests that the ES3 S -ES6 S base-pairing interaction is also conserved in mammalian 80S ribosomes (25).…”
Section: Comparison Of Expansion Segments Between Yeast and Wheat Germsupporting
confidence: 74%
“…Recently, a more comprehensive model of the yeast S. cerevisiae ribosome was built on the basis of an 8.9-Å cryo-EM reconstruction of a 80S ribosome from a related thermophilic fungus, Thermomyces lanuginosus (24), which, however, shares only ∼85% sequence identity with S. cerevisiae rRNA. With the exception of ES10 L , ES27 L , and the tip of ES15 L , molecular models were built for all the remaining expansion segments and variable regions (24). Yet, a number of significant differences between the yeast model presented by Taylor et al (24) and the yeast model presented here are evident (Fig.…”
Section: Comparison Of Expansion Segments Between Yeast and Wheat Germmentioning
confidence: 70%
See 1 more Smart Citation
“…Using rigid-body fitting of domains while making use of a published cryo-EM map of the yeast ribosome (26) for reference, we observe combinations of four motions previously described in the literature and associated with the elongation cycle, as follows: (i) ratchet-like intersubunit rotation, a counterclockwise rotation of the small subunit about an axis normal to the subunit interface (Fig. 3A, solvent view) (27,28); (ii) rotation (closing movement) of the L1 stalk toward the intersubunit space (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7), although the studies reported here do not provide any evidence for such dimerization. On the basis of the crystal structure of RPS19 from Pyrococcus abyssi, cryoelectron microscopy (cryo-EM) mapping, and the x-ray structure of the yeast ribosome, the location of RPS19 has been mapped to the head region of the 40 S subunit where it is accessible for interaction with other molecules (61,62). It is likely that the N-RPS19 interaction would recruit N at the head region of the 40 S subunit.…”
Section: Discussionmentioning
confidence: 99%